Spall Behaviors of Metaconcrete: 3D Meso-Scale Modelling - Jin, H.; Hao, Hong; Chen, Wensu; Xu, Cheng (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
Spalling is a typical tensile fracture phenomenon due to insufficient tensile strength of concrete. Concrete structure might experience severe spall damage at the rear surface of the structure owing to reflected tensile stress wave induced by impulsive load. In recent years, metaconcrete consisting of engineered aggregates has attracted attentions as metaconcrete exhibits extraordinary wave-filtering characteristics. Metaconcrete can be used to attenuate stress wave generated by impulsive load and hence possibly mitigate the spall damage. In this study, engineered aggregate is designed via the software COMSOL to have the frequency bandgap coincide with the dominant frequency band of stress wave propagating in the normal concrete (NC) specimen to reduce the stress wave propagation and hence spall damage. The wave propagation behaviors in metaconcrete specimen with periodically distributed engineered aggregates have been investigated in a previous study. This study establishes 3D meso-scale model of metaconcrete including mortar, randomly distributed natural aggregates and engineered aggregates to simulate spall behaviors of metaconcrete via the software LS-DYNA. The responses of metaconcrete composed of engineered aggregates with single bandgap and multiple bandgaps are studied. The results show that stress wave can be more effectively attenuated by using engineered aggregates with multiple bandgaps. It is found that although engineered aggregates mitigate stress wave propagation, the soft coating of the engineered aggregates reduces the concrete material strength, therefore spall damage of metaconcrete specimen is not necessarily less severe than the normal concrete, but has different damage mode. In addition, the influences of loading intensity and duration on stress wave, as well as the spall behaviors of metaconcrete specimen are also studied.